The Role of Histamine and Histamine Receptors in Mast Cell-Mediated Allergy and Inflammation: The Hunt for New Therapeutic Targets - Thangam, Elden Berla; Jemima, Ebenezer Angel; Singh, Himadri; Baig, Mirza Saqib; Khan, Mahejibin; Mathias, Clinton B.; Church, Martin K.; Saluja, Rohit (Frontiers in Immunology, 2018)
Histamine and its receptors (H1R-H4R) play a vital role in the development of various allergic and inflammatory diseases.Mast cells (MCs) are multifunctional, bone marrow-derived, tissue-dwelling cells, and are a major producer of histamine. In addition, mast cells can also respond to histamine, and the activation of histamine receptors (HR) such as H4R on mast cells can further amplify histamine-induced allergic responses. Both H1R and H4Rhave been found to play a major role in the progression and modulation of histamine-mediated allergic diseases. However, antihistamines that target H1Ralone are ineffective in the treatment of atopic dermatitis, allergic asthma, acute pruritus and other allergic diseases. Interestingly, antagonists that target H4Rhave shown promising effects in preclinical and clinical studies in the treatment of various allergic diseases. In this review, we examine the accumulating evidence suggesting novel therapeutic approaches that explore both H1R and H4Ras targets for the treatment of histamine-mediated allergic inflammatory diseases.